2016
DOI: 10.1177/0961203316640367
|View full text |Cite
|
Sign up to set email alerts
|

Preventing the development of SLE: identifying risk factors and proposing pathways for clinical care

Abstract: Although challenging, developing evidence-based approaches to an early and accurate diagnosis of systemic lupus erythematosus is a key approach to preventing disease and lupus-associated morbidity and mortality. Advances in our understanding of preclinical and incomplete lupus erythematosus have enabled the identification of risk factors that may predict disease and the development of potential strategies aimed at primary prevention. Emerging data support the notion that there is a temporal disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 161 publications
0
26
0
1
Order By: Relevance
“…Use of HCQ in early disease stages has been proposed as a preventive strategy in SLE [15]. To develop insights into this approach, the SLE and ILE patients were further examined in subgroups defined by current HCQ usage.…”
Section: Resultsmentioning
confidence: 99%
“…Use of HCQ in early disease stages has been proposed as a preventive strategy in SLE [15]. To develop insights into this approach, the SLE and ILE patients were further examined in subgroups defined by current HCQ usage.…”
Section: Resultsmentioning
confidence: 99%
“…Biomarkers such as autoantibodies and a variety of immune‐related and inflammation‐related molecules can appear years prior to clinical symptoms and/or the diagnosis of SLE and can accrue over time . Therefore, longitudinal studies are needed to evaluate the serologic status of anticellular antibody–negative and isolated CMP–positive patients over time and to evaluate whether the status varies with disease activity, damage accrual, therapeutic interventions, and/or specific substrate assays.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that serum biomarkers such as type II IFN cytokines appear years before SLE diagnosis, followed by anti-dsDNA autoantibodies and then by type I IFN activity immediately preceding clinical diagnosis, bringing forth the notion that they might be exploited in the potential prevention of SLE [810]. These studies support the concept of a gradual chronological disease progression, from a preclinical asymptomatic phase, to incomplete lupus erythematosus, and finally, to complete lupus erythematosus [149]. Clinical and serologic parameters distinguish patients with incomplete lupus from SLE patients, and identification of these parameters is crucial for early management of disease [150152].…”
Section: Biologics and Biomarkers In The Treatment And Diagnosis Of Slementioning
confidence: 92%